A Basic Review for Understanding the Important Role of Safety Instrumented Systems: Delivering through Lecture-based Classes - Arief Goeritno; Setyawan Widyarto; Irham Muhammad Azama; Nesia Andriana; Indriya Indriya; Roy Waluyo (Journal of Applied Science and Advanced Engineering, 2023)
A basic review is the process of studying a topic once more; thus, it can be used to understand something. In this case, safety instrumented systems are crucial and equipped by the reference to the six foundations, which include definition, knowledge base, terminology, structure, methodology, and epistemology, which was the background for the choice of the title. Therefore, it is necessary to understand the important role of safety-related systems, which are closely related to instrumentation and process control, through a lecture. This involves understanding several theories, in particular Bloom and Marzano's taxonomy. The research objectives are to work out the variety of sensors or detectors, to determine one of the many logic solvers, and to determine the final elements, especially emergency valves. The research methods are an algorithm of a researcher in conducting the research, in terms of performance, according to research objectives, and it was done in the form of a flow chart. The results are several flowchart structures to expose the stages of a brief explanation of the components of safety instrumented systems, including sensors, logic solvers, and final elements. The conclusion associated with research objectives is that the understanding of the important role of safety instrumented systems can be carried out through a lecture-based learning process.